(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
This study is aimed at identifying key issues in the staffing of health care organizations in the Kyrgyz Republic, which allowed developing recommendations to eliminate the identified causes of the shortage of medical workers. The analysis highlighted current issues related to the shortage of medical personnel and its outflow in the conditions of the modern labor market. The focus is on factors influencing the personnel situation, namely the staffing of medical institutions, including the percentage of employment of medical workers, including part-time, an analysis of the turnover of medical personnel, calculations of the staffing of medical organizations and the level of wages. The results of this analysis may be useful for government agencies, professional associations and research institutions seeking to improve the efficiency of the country’s healthcare system.